Nutrition a key to good health - Narayan, Susan (Gale Group/Thomson Learning, 2002)
Presents tables, charts, and discussions of statistics on nutrition in the U.S., covering such topics as agriculture, food spending, labeling, and obesity, and provides a list of further resources and a directory of organizations.